2020
DOI: 10.1186/s12910-020-00563-6
|View full text |Cite
|
Sign up to set email alerts
|

Sharing genomic data from clinical testing with researchers: public survey of expectations of clinical genomic data management in Queensland, Australia

Abstract: Background There has been considerable investment and strategic planning to introduce genomic testing into Australia’s public health system. As more patients’ genomic data is being held by the public health system, there will be increased requests from researchers to access this data. It is important that public policy reflects public expectations for how genomic data that is generated from clinical tests is used. To inform public policy and discussions around genomic data sharing, we sought public opinions on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 19 publications
0
26
1
Order By: Relevance
“…This finding is important for interpreting the prior literature on consent preferences for data sharing. Public attitudes vary greatly on the need for consent [ 12 , 35 ], with some people expecting to consent for each data use [ 9 ], some willing to provide one time (broad) consent [ 36 , 37 , 38 ] and some happy for data to be used without consent [ 19 , 39 ]: two thirds of the participants in our study indicated that they were willing to share de-identified health data with institutions for IRB-approved research without specific consent. It is tempting to attribute the apparent differences between the relative weight given to consent in this study compared with others in Northern America and Europe to cultural norms in Asia that are assumed to place less emphasis on individual liberty and consent.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This finding is important for interpreting the prior literature on consent preferences for data sharing. Public attitudes vary greatly on the need for consent [ 12 , 35 ], with some people expecting to consent for each data use [ 9 ], some willing to provide one time (broad) consent [ 36 , 37 , 38 ] and some happy for data to be used without consent [ 19 , 39 ]: two thirds of the participants in our study indicated that they were willing to share de-identified health data with institutions for IRB-approved research without specific consent. It is tempting to attribute the apparent differences between the relative weight given to consent in this study compared with others in Northern America and Europe to cultural norms in Asia that are assumed to place less emphasis on individual liberty and consent.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has shown general public reluctance to share data with commercial companies [ 8 , 9 , 46 ], primarily due to concerns about exploitation/profiteering [ 39 , 47 ] and a lack of familiarity [ 48 , 49 ] with intended uses of the data by commercial companies. However, there is limited research that differentiates between different commercial entities with an interest in health data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sixteen Capability projects were commissioned within the Strategy and Legacy Rounds (Table 2 ). Projects focused on (1) preparation of the health system for genomics, or (2) support or evaluation of Clinical projects 27 – 35 . In addition, seven projects designed by the CAG were funded in the Strategy and Legacy Rounds (Table 2 ) that focused on areas of need for the patient community and patient support mechanisms within the health system 36 .…”
Section: Program Activitiesmentioning
confidence: 99%